Kinematics Analysis of Spatial 8R Hip Joint Rehabilitation Parallel Mechanism - Zengyu Jia; Ruiqin Li; Xiang Li (Jixie chuandong)
A 2-DOF spatial 8R parallel mechanism is proposed for hip joint rehabilitation. The model of spatial 8R parallel mechanism is established， and the initial configuration and general configuration of the mechanism are analyzed by using screw theory. The geometric model and kinematics equations of the spatial 8R parallel mechanism are established by D-H method， and the kinematics equations of the mechanism are obtained. The correctness of the kinematics equation of the spatial 8R parallel mechanism is verified by Adams software and theoretical calculation， and the variation law of the angular displacement of the mechanism in one period under different motions is obtained. This spatial 8R parallel mechanism has stable performance and can carry out smooth movement， which can effectively improve the rehabilitation effect of hip joint.